Donations to increase productivity in public good production: Experimental evidence - Natalie Struwe; Esther Blanco; James Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
This research is inspired by in-kind donations that have the capacity to increase the marginal benefit (productivity) in provision of public goods, for example by providing critical infrastructure that increases the productivity of resources utilized by local public good providers. We provide experimental evidence from a twostage decision environment where donors (outsiders), who benefit from a public good, send transfer donations to providers (insiders) of the public good, who also receive benefits. We find that that donors are willing to offer transfers at a sufficiently high level to increase the productivity (MPCR) of the public good. Public good provision by insiders, however, is neither increased significantly above levels observed in treatments with the same MPCR where outsiders' donations are used as compensation rewards to insiders, nor in treatments without donations. Thus, whether a given MPCR is reached endogenously through donations by outsiders or exogenously does not significantly affect insiders' public good provision. In addition, when comparing continuous to threshold endogenous changes in the MPCR, we cannot find significant differences in public good provision, despite transfer donations by outsiders are higher for threshold increases in the MPCR.
Keywords: D70; D62; D64; H41; 330; Public goods; Privately Provided Public Goods; Institution; Externality; Donation; Reciprocity